2020
DOI: 10.1038/s41586-020-2760-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the action of the drug trametinib at KSR-bound MEK

Abstract: The M APK/ E RK K inase MEK is a shared effector of the frequent cancer drivers KRAS and BRAF that has long been pursued as a drug target in oncology 1 , and more recently in immunotherapy 2 , 3 and aging 4 . However, many MEK inhibitors (MEKi) are limited due to on-target toxicities 5 – 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 47 publications
4
91
0
Order By: Relevance
“…RAF and MEK interact with KSR1, an inactive pseudokinase that is structurally related to RAF. Interestingly, trametinib causes MEK to engage KSR1 more effectively, which may facilitate the ability of particular combinations of RAF and MEK inhibitors to target RAF–KSR–MEK complexes 60 . The first dual RAF–MEK inhibitor VS6766 (also known as CH5126766) has entered phase I clinical trials and has shown some efficacy in solid tumours and in multiple myeloma harbouring various RAS–RAF mutations 61 .…”
Section: Trends In Targeting Tyrosine Kinase Activitymentioning
confidence: 99%
“…RAF and MEK interact with KSR1, an inactive pseudokinase that is structurally related to RAF. Interestingly, trametinib causes MEK to engage KSR1 more effectively, which may facilitate the ability of particular combinations of RAF and MEK inhibitors to target RAF–KSR–MEK complexes 60 . The first dual RAF–MEK inhibitor VS6766 (also known as CH5126766) has entered phase I clinical trials and has shown some efficacy in solid tumours and in multiple myeloma harbouring various RAS–RAF mutations 61 .…”
Section: Trends In Targeting Tyrosine Kinase Activitymentioning
confidence: 99%
“…An elegant recent study demonstrated that the MEK1 inhibitor Trametinib binds in a manner that enhances stability of a KSR-MEK1 complex ( Fig. 7 ; ( 107 )). Not only does this binding mode enhance residency of the inhibitor on MEK1, but the KSR-MEK1 complex is stabilized relative to the RAF-MEK1 complex, diminishing signaling flux through the pathway.…”
Section: Small-molecule Modulation Of Noncatalytic Kinase Functionmentioning
confidence: 99%
“…
Figure 7 Structure of the MEK1-KSR2-Trametinib complex. The overall structure of MEK1 ( tan ) binding to the KSR2 pseudokinase domain ( gray ; PDB 7jur; ( 107 )). An inset view below illustrates the intimate relationship between the MEK1 activation loop and Trametinib, which is stabilized by KSR2.
…”
Section: Small-molecule Modulation Of Noncatalytic Kinase Functionmentioning
confidence: 99%
“…KSR1 contains a tyrosine within a conserved motif from the NtA region ( Figure 2 ), which could explain why KSR1 is able to transactivate BRAF unlike KSR2 [ 55 ]. A recent study has also shown the potential of targeting KSR1/2:MEK1/2 complexes, offering a potential therapeutic approach for targeting aberrant ERK1/2 signalling [ 56 , 57 ].…”
Section: The Structure Of Raf Proteinsmentioning
confidence: 99%